An Investigation and Evaluation of Cross- Border Truck Transportation Between Nongkhai, Thailand – Thanaleng to Vientiane, Lao PDR - Sisalermkiat Phandanouvong; Suthep Nimsai (International Journal of Supply Chain Management, 2018)
Lao PDR has been a large constraint in the international mark accessibility for its economic development for a long time. Moreover, Lao PDR depends on its neighbors as its key transit countries by using their sea ports, thus cross-border truck transportation development becomes an essential for substantial economic development for Lao PDR. Therefore, the government of Lao PDR has its policy to transform its landlocked country to be as a land linked country by focusing on improving and developing the infrastructure to connect and integrate to sub-regional and regional. The purpose of this research is to identify and investigate the barriers and the impediments to seamless cross-border truck transportation between Thailand and Lao PDR and to use cross-border truck transportation from Nongkhai-Thanaleng to Vientiane, Lao PDR as an illustrative case study. The Analytic Hierarchy Process (AHP) to figure out the cost, time, and reliability as the key factors. From the outcome, it found that the cost of transportation service provider was the most important factor, which effected to cross-border tuck transportation was the highest weight 0.5889. Nevertheless, the experts from both government and business sectors who had many working experiences on Nongkhai to Thanaleng route are considering about improving the transportation service to supply the higher demand in current situation. This study could be beneficial guideline for strategy development and forming competitive advantages of cross-border truck transportation.